History of Transylvania - Koopeczi, Bela; Makkai, Laszlo, 1914-1989; Moocsy, Andras; Szasz , Zoltan (Atlantic studies on society in change ;, 2002)
These volumes of a three-volume history of Transylvania are designed to present Transylvanian history in a European context and with due attention to Transylvania's links to Hungary, the Habsburg Empire, the Romanian Principalities, Turkey and other states of Europe. The comparative approach is also prominent in the presentation of Transylvania's internal affairs in that the authors address the history-demographic, economic, social, political and cultural-of the three major national groups: Romanian, Hungarian, and Saxon.